(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Aluminium dross is a by-product of aluminium production. At present, dross is processed in rotary kilns to recover the aluminium. The objective of present work is to utilize the aluminium dross in the natural cycle (closed loop) by using it as an engineered material and to investigate the mechanical properties of new concrete type obtained by adding aluminium dross which is an impure aluminium mixture that results from metals melting and mixing with flux. The main advantage of this type of concrete over the conventional ones is the reduction in the quantity of raw materials.